The Effect of Green Grape Extract on Serum Triglyceride Levels in Rats: Pengaruh Pemberian Ekstrak Anggur Hijau terhadap Kadar Triglierida Serum pada Tikus - Bekti, Heri Setiyo; Dewi, Ni Nyoman Astika; Rinawati, Luh Putu; Dewi, Ni Wayan Rika Kumara; Hadi, Mochammad Choirul (Medicra (Journal of Medical Laboratory Science/Technology), 2024)
Cardiovascular disease, one of which is coronary heart disease (CHD) is the main cause of death and morbidity caused by blockages in the coronary arteries (atherosclerosis). Elevated serum triglyceride levels can encourage the formation of atherosclerosis. Statins are the drugs most commonly used to lower triglyceride levels but have side effects, so new treatment are needed. Grapes are fruits that has many bioactive compounds such as proanthocyanidins and resveratrol which are believed to reduce triglyceride levels in serum. The purpose of this study was to determine the effect of green grape extract (Vitis vinifera) on triglyceride levels in male Wistar rats which were divided into 5 groups, namely P0 (fed with standard feed), P1 (fed with high cholesterol and then standard feed), P2 (fed with high cholesterol and simvastatin 0.2mg/200mgBW/day), P3 (fed with high cholesterol and grape extract at a dose of 500mg/200mgBW/day), and P4 (fed with high cholesterol and 250mg/200mgBW/day grape extract). Examination of triglyceride levels was carried out using the GPO-PAP method. Data analysis was performed with Annova test followed by Bonferroni test. The statistical test results showed that there were significant differences between each treatment group. The P3 group showed a lower average triglyceride level than P4 although it was still higher than P2. This showed that administration of green grape extract has an effect on decreasing serum triglyceride levels in all.